Factors That Infl uence the Revaluation of Fixed Assets in Manufacturing Sector Companies Listed on the Indonesia Stock Exchange Period 2014-2017 - Fadhilah Amelinda; Nur Suci I Mei Murni (Universitas Hayam Wuruk Perbanas, 2018)
This study aims to determine the effect of leverage, liquidity, fi xed assets intensity, and fi rm size on the revaluation of fi xed assets. The population of this study is manufacturing sector companies in Indonesia. The research samples are manufacturing companies listed on the Indonesia Stock Exchange in 2014 - 2017. Sampling technique is conducted using purposive sampling method. TheÂ data used are secondary data. The research data include fi nancial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) obtained from ww.idx.co.id in 2014-2017. The data collection strategy in this study is the archive strategy, that is, the data collection derived from existing records or databases. Data analysis is done using logistic regression analysis. The results of this study show that the variables of leverage, liquidity, and fi xed assets intensity have no effect on the companyâ€™s decision to carry out fi xed assets revaluation, while the variable of fi rm size has an effect on the companyâ€™s decision to carry out fixed assets revaluation.